The Impact of Content Moderation Policy on the Spread of Fake News on Social Media in Indonesia - Febryani, Evy (Eastasouth Institute, 2025)
This research investigates the impact of content moderation policies on the spread of hoax news on social media platforms in Indonesia, employing a normative legal analysis approach. The study examines the effectiveness of existing legal frameworks, such as the Electronic Information and Transactions Law (ITE Law), and evaluates content moderation mechanisms employed by both the government and social media platforms. Findings indicate that while the ITE Law provides a legal basis for addressing misinformation, its vague provisions and potential for misuse have raised concerns regarding freedom of speech. Additionally, content moderation efforts by the government and social media platforms face challenges due to technological limitations, inconsistent enforcement, and a lack of public awareness. The study also highlights the need for a more integrated, multi-stakeholder approach to combat hoax news effectively. The research concludes that while current content moderation policies have had some success, their full impact is constrained by legal, technological, and social challenges. To improve the effectiveness of these policies, the study recommends clearer legal frameworks, enhanced technological capabilities, increased media literacy, and stronger coordination among stakeholders.